Contribution to the taxonomic knowledge of Ampharetidae (Annelida) from Antarctica with the description of Amage giacomobovei sp. nov. - Schiaparelli, Stefano; Jirkov, Igor A. (European Journal of Taxonomy, 2021)
Thanks to newly collected material from the Terra Nova Bay area (Ross Sea, Antarctica), we discuss the taxonomy of the ampharetid genera Amage Malmgren, 1866 and Amythas Benham, 1921. A new species of Amage, A. giacomobovei sp. nov., is described based on morpho-anatomical data. This is the second new species described from an area which appears to be rich in ampharetids, a coastal embayment at ~500 m depth near the Italian “Mario Zucchelli” research station. The new species is characterized by having 16 abdominal uncinigers and four pairs of branchiae that readily distinguish it from its congeners. Tubes of A. giacomobovei sp. nov. are also characteristic in showing a large amount of embedded sponge spicules, suggesting a possible close association to spicule mats. Based on the amended diagnoses of the two genera, Amage septemdecima Schüller & Jirkov, 2013 is transferred to the genus Amythas. Finally, to simplify the task of ampharetid genera recognition for untrained people, we provide a dichotomic key for ampharetid genera found in Antarctica and a checklist of species occurring in Terra Nova Bay.